2015
DOI: 10.1177/1747493015607516
|View full text |Cite
|
Sign up to set email alerts
|

Single photon emission computed tomography imaging of cerebral blood flow, blood–brain barrier disruption, and apoptosis time course after focal cerebral ischemia in rats

Abstract: Using SPECT/CT imaging, we showed that after transient middle cerebral artery occlusion in rat there was a sustained decrease in cerebral blood flow followed by blood-brain barrier disruption preceding meanwhile apoptosis. Rodent SPECT/CT imaging of cerebral blood flow, blood-brain barrier disruption and apoptosis appears to be an efficient tool for evaluating neuroprotective drugs and regenerative therapies against cerebral ischemia and time-windows for therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…ECFC are considered to be the relevant endothelial progenitors due to their specific vasculogenic activity [11,12]. We previously showed that intravenous administration of ECFC contributed to vascular recovery, limited tissue injury after hind limb ischemia, and transient cerebral ischemia in adult rodents [14,15,[32][33][34][35]. In all these models, ECFC administration was associated with a decrease in apoptosis, a growth factor release enhancement and a neovascularization stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…ECFC are considered to be the relevant endothelial progenitors due to their specific vasculogenic activity [11,12]. We previously showed that intravenous administration of ECFC contributed to vascular recovery, limited tissue injury after hind limb ischemia, and transient cerebral ischemia in adult rodents [14,15,[32][33][34][35]. In all these models, ECFC administration was associated with a decrease in apoptosis, a growth factor release enhancement and a neovascularization stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of isotope entry with SPECT imaging is done voxel by voxel to assess radioactivity concentration (absolute or relative) within varied brain regions. This technique is known to be less sensitive for smaller lesions or less disrupted areas [2527]. CT has been shown to be more sensitive than SPECT in detecting smaller areas of BBB disruption because SPECT results in low spatial resolution [22].…”
Section: Introductionmentioning
confidence: 99%
“…Increased expression of apoptotic proteins, including phosphorylated (p)-Arabidopsis serine/threonine kinase 1 (ASK1), p-c-Jun N-terminal kinase (JNK), p-p38, cleaved caspase-3 and cytochrome c in the ischemic penumbra has been observed following stroke ( 177 ). Studies have reported that the inhibition of apoptosis may prevent the development of cerebral ischemia/reperfusion injury ( 166 , 180 185 ). Thioredoxin-1 (Trx1) small interfering RNA increases ASK1 activation in response to apoptotic stress, Trx1 may therefore be anti-apoptotic and suppress cerebral ischemia/reperfusion injury ( 186 188 ), potentially via inhibition of the ASK1-JNK/p38 signaling pathway.…”
Section: Notch Signaling and Apoptosis In Cerebrovascular Diseasesmentioning
confidence: 99%